ANALYSIS OF THE INFLUENCE OF REGIONAL CAPITAL EXPENDITURE, INVESTMENT PRIVATE ENTERPRISE, LABOR AND SPECIAL ALLOCATION FUNDSON THE ECONOMIC GROWTH OF ACEH PROVINCE - M. Nur Akarim; Fitri Rahmadana; Muhammad Yusuf; Ainul Mardhiyah; Arwansyah; Khairani Alawiyah Matondang; Fitrawaty (RADJA PUBLIKA, 2026)
This study aims to analyze the effect of capital expenditure on regional economic growth in Aceh Province by considering control variables and the Special Autonomy Fund (DOKA) as a moderating variable. The control variables include the Open Unemployment Rate (TPT), Labor Force Participation Rate (TPAK), Human Development Index (HDI), and investment. This study employs panel data covering 23 regencies/cities over the period 2016–2025. The analytical method used is panel data regression with a Fixed Effect Model (FEM), selected based on the Chow test and Hausman test. Estimation is conducted using robust standard errors (White cross-section) to address potential heteroskedasticity and autocorrelation issues. The results indicate that capital expenditure has a positive and significant effect on economic growth. The HDI and investment variables also show positive and significant effects, while TPT and TPAK are not statistically significant. DOKA has a positive effect on economic growth; however, the interaction between capital expenditure and DOKA shows a significant negative effect, indicating that DOKA tends to weaken the effectiveness of capital expenditure. These findings highlight the importance of improving fiscal governance quality so that capital expenditure and DOKA can be more effective in promoting regional economic growth.